2001
DOI: 10.1007/s11325-001-0123-4
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Competence in Eliciting a History for “Chronic Fatigue”

Abstract: A majority of students do not adequately cover issues relevant to sleep in contrast to other associated disorders when taking a focused history for chronic fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
1
2
Order By: Relevance
“…Our study also revealed that 46.3% of the participants classified as unwell with fatigue and 19.9% of those classified as unwell but without fatigue endorsed persistent problems staying awake during the day, which suggests that the perception of sleepiness is discernable from a sense of fatigue. This unanticipated finding diverges from the findings of other studies suggesting that patients and clinicians may not readily distinguish between symptoms of sleepiness and fatigue ( 34 ). We speculate that our methodological approach, detailed questionnaires, and structured telephone interview differed significantly from those used by prior investigators and may have contributed to this finding.…”
Section: Discussioncontrasting
confidence: 85%
“…Our study also revealed that 46.3% of the participants classified as unwell with fatigue and 19.9% of those classified as unwell but without fatigue endorsed persistent problems staying awake during the day, which suggests that the perception of sleepiness is discernable from a sense of fatigue. This unanticipated finding diverges from the findings of other studies suggesting that patients and clinicians may not readily distinguish between symptoms of sleepiness and fatigue ( 34 ). We speculate that our methodological approach, detailed questionnaires, and structured telephone interview differed significantly from those used by prior investigators and may have contributed to this finding.…”
Section: Discussioncontrasting
confidence: 85%
“…This study indicates that the element of history taking is implemented at a very high level by respondents (97.2%). The result obtained, is contrary to the study by Papp et al (2001). Furthermore, 90.5% of respondent carry out almost all the skills in element of the concrete solution.…”
Section: The Combination Of Doctor-centred and Patient-centred Style And Information Seeking Practicecontrasting
confidence: 83%
“…Knowledge is generally tested by written examination, but there is increasing interest in complementary assessments, such as observed patient interactions, simulated patients, structured clinical encounters, or chart review, as outcomes for assessment during training (14). An array of assessment tools is available (16)(17)(18) or new tools can be constructed from the competency objectives. The online supplement provides examples of assessments.…”
Section: Assessment Toolsmentioning
confidence: 99%